Sustainability Assessments of Buildings - Umberto Berardi (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
International research has confirmed that the built environment is the most promising sector for a rapid transition to sustainability. In this scenario, many examples of sustainable urban environments are showing the advantages of sustainability. Meanwhile, an increasing request for tools to assess their sustainability is recorded. The assessment of sustainability of the built environment is an essential step toward its promotion. However, large difficulties exist creating useful and measurable assessment indicators since sustainability is time- and location-dependent. Meanwhile, the need to assess both products and processes for sustainable buildings has been considered particularly important for a sector as inertial as that of the built environment. This books contains ten recently published papers in the Special Issue about "Sustainability assessments of buildings". The demand for this Special Issue raised from the floor, as more and more papers dealing with this topic were submitted to Sustainability in the last few months. The need to collect the recent research in this field became evident, and the respond to the call showed the high attention of the scientific community towards this topic. A selection of ten papers among those published in the special issue will guide the reader thorough the variety of approaches in sustainability assessments of buildings and their main challenges.